Hubungan Promosi melalui Media Sosial Instagram dengan Minat Travelling pada Himpunan Mahasiswa Cirebon di Karawang - Nurhidayah, Widia; Lubis, Flori Mardiani; Nurkinan, Nurkinan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The lifestyle of people who move fast and are in direct contact with the internet, has caused the promotion model to be very relevant to be applied to both tourist destinations and tourism accommodation managers to do good imagery, recently it has graced the Instagram timeline of the many Instagram accounts that promote Indonesian tourism, especially regency areas. Majalengka, namely the Instagram account @exploremajalengka. The purpose of this study was to determine the effect of the Instagram account @exploremajalengka promoting tourist objects or attractions on tourists' interest in visiting tourist attractions in Majalengka. This research uses a quantitative methodology and approach. The population in this study is the Cirebon Karawang Student Association (HIMACIKA) followers from the @exploremajalengka account which are known to number 70 people. The sample in this study were 60 respondents. The results of this study through a questionnaire research instrument. The percentage of variable X (Instagram account @exploremajalengka) is 92.5% and is categorized as very good. The percentage of the variable Y (interest in visiting tourist attractions in Majalengka) is 94.25% and is categorized as very good. The Product Moment correlation value between variables X (to Y) shows a number of 0.627, the correlation value of the relationship between the account variable @exploremajalengka and the variable interest in visiting (traveling) to tourist spots in Majalengka, the relationship between the two variables has a strong value. The determining coefficient (determination) shows that the R square value is 0.947, meaning that the correlation between variable X and variable Y is 94.7% and the rest is determined by other factors. The linear regression equation in this study is Y = 10.57 + 0.28 X. The t test shows that the independent variable has a specification of less than 0.05, tcount (3.809) > ttable (1.671). The F test on variable X on variable Y is 31.345 greater than F table 4.001.